PERLINDUNGAN KONSUMEN DALAM PENERAPAN BATAS KEWENANGAN BADAN PENYELESAIAN SENGKETA KONSUMEN MENYELESAIKAN PERKARA KONSUMEN (Studi Putusan No 481 K/Pdt.Sus-BPSK/2015) - Takenia Tifany; Anna Maria Tri Anggraini (Jurnal Hukum Adigama, 2018)
Consumer Protection Law regulates the legal protection of consumer and including Consumer Dispute Completion Firm who autorhized to resolve consumer disputes who feel harmed over the acts of business from people that sometimes arbitrary, but decisions taken by Consumer Dispute Completion Firm often incriminate business actors, and usually seem to exceed the limit of their authority even wrong in applying the law. Consumer Dispute Completion Firm’s authority to adjudicate and decide a dispute is induced by Supreme Court’s decision which makes Consumer Dispute Completion Firm’s authority to limited. Therefore, the writer proposed an issue about how are the limits of Consumer Dispute Completion Firm’s authority in adjudicate and decide a consumer disputes? And how are the implementation and Supreme Court’s views regarding the limitation of Consumer Dispute Completion Firm’s authority? The writer examines the problem using normative legal research methods that use secondary data. From the results of the research, it can be concluded that the limits of Consumer Dispute Completion Firm authority in solving consumer disputes are limited to the agreement between both parties. In sense the Supreme Court believes that all transactions based on an agreement become the jurisdiction of the court